APPLICATION EXPERIENCE OF COMPUTER SIMULATION SYSTEMS TO INCREASE THE EFFICIENCY OF FOUNDRY PRODUCTION AT THE ROSTOV FOUNDRY - A. V. Fedosov; G. V. Chumachenko (Литьë и металлургия)
The stages of introduction of computer simulation tools in the production process of The Rostov Foundry are considered. A system for estimating the results of simulation is proposed, which includes the definition of complex parameters that allow an assessment of the causes and the probability of formation of shrinkage defects. An equation that determines a relationship between results of simulation and actual rejects in production is proposed. The feeder operation index is suggested to use for estimation of the reasons for the formation of shrinkage defects. The yield index is suggested to evaluate the possibility of reducing the weight of gate system. Equations for calculating of these indices are developed. A systematic approach is presented for the application of simulation results, which provides for the organization of a database of the technologies being studied. The development of this base allows not only to accumulate the experience, but also to apply it to minimize errors and save time in the process of introducing new castings. The results of practical application of the developed system for 10 positions are presented, which allowed to increase the yield by 6.9% and to reduce the total defects rate by 5.1%.